Proceso de ASC - PENSAMIENTO SISTEMICO Y NEGOCIOS PARA EL FLORECIMIENTO DE LA VIDA (2023)
The students from the research group designed training workshops for entrepreneurs based on their knowledge of the Flourishing Business Model Canvas and the importance of systems thinking in the design and validation processes of sustainable business models. The workshops were conducted with five entrepreneurs who received 25 hours of support from the students.